The importance for journals to publish commentaries and letters to the editor in the age of COVID-19 - Teixeira da Silva, Jaime A. (International Journal Of Community Medicine And Public Health, 2021)
Letters to the editor (L2Es) and commentaries play an essential role in science communication and in critical analysis of the biomedical literature. This importance could not be more profound or more pertinent than now, in the midst of the COVID-19 pandemic, where there is considerable need to openly, transparently and urgently discuss medical findings related to healthcare. L2Es and commentaries offer fair opportunity for authors to comment on matters of general interest, or to challenge the findings of published papers, without fearing any risk of retaliation while being able to express their personal opinion about an issue that matters to them, and allowing the challenged authors to respond within an academic setting. It is important to expand this form of communication via L2Es and commentaries to biomedical and healthcare policy journals that might lack this option.